The Effect of Menstrual Cycle Physiological Changes on Physical Fitness Patterns in Middle School Students Aged 12-14 Years - Ziab, Hussein; Ayoub, Israa; Albanaa, Seleen; Alaaldeen, Hussaien; Hamood, Waleed (Journal of Physical Education, 2022)
The purpose of this study was to determine the effect of the physiological changes associated with the menstrual cycle on some aspects of physical fitness, specifically speed, agility, and flexibility, among middle school students in Beirut aged 12 to 14 years old. To accomplish this, the study was conducted on a sample of 21 female students who were in good health and had a regular monthly cycle, and the descriptive approach was used to suit the nature of the study. Time and speed during the slalom and 30-meter sprint tests, as well as distance achieved during the trunk flexion test, were measured before and after menstruation. The study's findings revealed statistically significant differences at the level (0.05) in all variables: time, speed, and distance. This demonstrates the effect of the menstrual cycle on the elements of physical fitness, which is the focus of our research. The researchers recommended that physical education programs for girls be aligned with menstrual cycle requirements, taking into account the importance and necessity of exercising and not stopping during this time.